Implementasi Pendidikan dan Pelatihan dalam Meningkatkan Kompetensi Guru Sekolah Dasar/Madrasah Ibtidaiyah di Desa Duren Kecamatan Klari Kabupaten Karawang - Rukaj, Ajat; Gusniar, Iwan Nugraha; Abas, Totoh Tauhidin; Nurkhalizah, Ervin; Bachruddin, Rizal (Al-DYAS, 2023)
The Management of Pedagogical Competence and Professional Competence Improvement for Elementary School Teachers through Education and Training (Diklat) must be continuously enhanced and intensified, and should be conducted well to achieve the Diklat goals from the planning stage to implementation and evaluation, even though there are still some weaknesses in the planning and execution of the Diklat. This is based on a preliminary study that found about 60% of elementary school teachers in Karawang Regency apparently have insufficient mastery of teaching competencies, especially in pedagogical and professional competencies. Meanwhile, among the prospective Diklat participants, 37 individuals (61.6%) claimed to have a sufficient grasp of pedagogical and professional competencies, while 23 individuals (38.3%) lacked mastery of these competencies. The Diklat planning process involves conducting a Need Assessment analysis of the training, including a strategic program analysis, a personal analysis of prospective participants and training instructors, and an analysis of tasks related to the training's content and objectives. The implementation phase begins with Diklat packages for Mathematics Adaptation, Science Adaptation, ICT Learning, and the Reading Program. Diklat activities are carried out gradually, starting with School Team Workshops (STW), Teacher Study Groups (KKG), and Teacher Coaching and Assistance Teams (KKKS). Participants, who are elementary school teachers, are trained by MI/SD supervisors and instructors from public and private higher education institutions (PTN/PTS) using inquiry, demonstration, role-playing, and problem-based learning methods. The Diklat is expected to enhance teachers' competency by achieving a high level of mastery of the training material. They should also have a good grasp of teaching competencies and be able to contribute to improving teacher performance. Despite some challenges encountered during its implementation, including: a. A small number of training instructors lacking professionalism in mastering the training material; b. The combination of teacher participants with different educational backgrounds, some having completed SPG/SLTA-equivalent education and others holding a Bachelor's degree, resulting in varying rates of material absorption and reduced motivation for learning among SPG/SLTA-equivalent graduates; c. Insufficient computer facilities for ICT lessons.